Diversity in the Regulation of Autophagy and Mitophagy: Lessons from Parkinson's Disease - Charleen T. Chu (Parkinson's Disease)
Selective mitochondrial degradation through autophagy (mitophagy) has emerged as an important homeostatic mechanism in a variety of organisms and contexts. Complete clearance of mitochondria can be observed during normal maturation of certain mammalian cell types, and during certain forms of neuronal cell death. In recent years, autophagy dysregulation has been implicated in toxin-injured dopaminergic neurons as well as in major genetic models of Parkinson's disease (PD), including α-synuclein, leucine-rich repeat kinase 2 (LRRK2), parkin, PTEN-induced kinase 1 (PINK1), and DJ-1. Indeed, PINK1-parkin interactions may form the basis of a mechanism by which dissipation of the inner mitochondrial membrane potential can trigger selective mitochondrial targeting for autophagy. Multiple signals are likely to exist, however, depending upon the trigger for mitophagy. Similarly, the regulation of basal or injury-induced autophagy does not always follow canonical pathways described for nutrient deprivation. Implications of this regulatory diversity are discussed in the context of neuronal function and survival. Further studies are needed to address whether alterations in autophagy regulation play a directly injurious role in PD pathogenesis, or if the observed changes reflect impaired, appropriate, or excessive autophagic responses to other forms of cellular injury.